Polypropylene carbonate-based composite membrane and preparation method thereof
A composite film with a PBAT, modified PPC, and PLA structure, enhanced by specific additives, addresses thermal stability and mechanical strength issues, achieving superior barrier and mechanical performance for packaging applications.
Patent Information
- Application Number
- CN202411258061.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-09
AI Technical Summary
Existing composite films made from polylactic acid (PLA) and polycarbonate lactone (PPC) suffer from poor thermal stability, barrier properties, and mechanical strength, limiting their application in environmentally friendly packaging.
A composite film structure comprising a PBAT heat-sealing layer, a modified PPC layer, and a PLA layer, bonded by specific adhesive layers, utilizing a heat stabilizer, chain extender, and modified composite filler to enhance compatibility and interaction between layers.
The composite film exhibits excellent high barrier properties, thermal stability, and mechanical properties, making it suitable for environmentally friendly functional packaging.
Smart Images

Figure BDA0005034687260000121 
Figure BDA0005034687260000132
Abstract
Description
Technical Field
[0001] The invention relates to the field of packaging film material preparation, and in particular to a composite film based on polypropylene carbonate and a preparation method thereof. Background Art
[0002] With the improvement of living standards and the accelerated pace of life, the market demand for barrier membrane materials has increased. However, most of the current membrane materials are non-degradable and can easily cause environmental pollution after use and disposal. In order to reduce the damage of non-degradable membrane materials to the environment, it is particularly important to develop degradable membrane materials.
[0003] Polylactic acid (PLA) and polycarbonate lactone (PPC) are often used as biodegradable materials. Among them, polylactic acid has excellent optical transparency and mechanical strength, but poor toughness and barrier properties, which limit its application. Polycarbonate lactone is an alternating copolymer of carbon dioxide and propylene oxide, but the presence of ether bonds on the main chain of PPC makes it easy for the chain segments to rotate internally around the ether bonds, increasing the flexibility of the chain, and the highly polar carbonyl group increases the intermolecular force. The end group of PPC will affect the thermal stability of the material. Its end group is hydroxyl. At high temperature, the presence of hydroxyl will cause ester alcoholysis, resulting in "unzipping" degradation, which in turn makes the thermal stability of the single-structure layer PPC film product poor.
[0004] In the prior art, there is also a method of polymer blending, in which a mixture of two or more homopolymers or copolymers is blended to obtain a polymer blend. After the polymer blend is mixed with different polymer materials and dispersed, the mechanical properties and thermal stability of the PPC material are changed. For example, in the prior art, the PPC-P, PBAT and PLA materials are compounded and cast into a film, and the prepared film product has a certain biodegradability, but the overall barrier performance is poor. For example, the invention patent with Chinese patent application number CN202310756023.4 discloses a PPC-P degradable flexible film material, which is mainly made of the following raw materials: PPCP, PBAT and PLA, primary antioxidant, auxiliary antioxidant, opening agent, anti-hydrolysis agent, anti-ultraviolet agent, chain extender, plasticizer and compatibilizer. The film uses PBAT, PLA and additives to modify PPC-P, so that the film has good ductility and elongation at break, as well as good heat resistance and impact resistance and excellent air permeability and moisture permeability. However, the effect of the PBAT and PLA blending modification is limited, and the thermal stability, barrier properties and mechanical strength of the prepared film cannot be guaranteed at the same time, thus limiting its application. Summary of the invention
[0005] Based on this, in order to solve the problems of poor thermal stability, barrier properties and mechanical strength of the composite film prepared by the prior art, the present invention provides a composite film based on polypropylene carbonate and a preparation method thereof. The specific technical scheme is as follows:
[0006] A composite film based on polypropylene carbonate, comprising a PBAT heat-sealing layer, a modified PPC layer and a PLA layer, wherein the PBAT heat-sealing layer and the modified PPC layer are bonded to each other via a first bonding layer, and the modified PPC layer and the PLA layer are bonded to each other via a second bonding layer;
[0007] The PBAT heat seal layer comprises the following raw materials in parts by weight: 100 to 110 parts of PBAT, 7 to 12 parts of heat stabilizer, 1 to 5 parts of lubricant, and 5 to 15 parts of antioxidant;
[0008] The modified PPC layer comprises the following raw materials in parts by weight: 100 to 120 parts of PPC, 15 to 25 parts of chain extender, 1 to 10 parts of modified composite filler, and 1 to 7 parts of plasticizer A;
[0009] The PLA layer comprises the following raw materials in parts by weight: 80 to 100 parts of PLA, 10 to 15 parts of ethylene-acrylic acid copolymer, 1 to 5 parts of antioxidant, and 1 to 5 parts of plasticizer B;
[0010] The first adhesive layer and the second adhesive layer both include the following raw materials in parts by weight: 30 to 45 parts of polyvinyl alcohol, 25 to 35 parts of maleic anhydride grafted ethylene polymer, and 1 to 5 parts of a compatibilizer.
[0011] Furthermore, the heat stabilizer is prepared by mixing dioctyltin dilaurate and zinc stearate in a mass ratio of 1:(1-3).
[0012] Furthermore, the lubricant is at least one of stearic acid, aluminum stearate, calcium stearate and zinc stearate.
[0013] Furthermore, the compatibilizer is at least one of PP-g-MAH and ethylene-methyl acrylate copolymer.
[0014] Furthermore, the chain extender is at least one of isocyanate-maleic anhydride copolymer, styrene-maleic anhydride copolymer and hexamethylene diisocyanate.
[0015] Furthermore, the modified composite filler is obtained by mixing calcium carbonate and lignin cellulose in a mass ratio of (1-5):1 and then subjecting the mixture to modification treatment with a silane coupling agent.
[0016] Furthermore, the plasticizer A is at least one of poly(1,2-propylene succinate), glycerol and pentaerythritol.
[0017] Furthermore, the antioxidant is one of antioxidant 1076 and antioxidant 168 or a mixture of both.
[0018] Furthermore, the plasticizer B is at least one of tributyl citrate, acetyl triethyl citrate, and acetyl tributyl citrate.
[0019] In addition, the present invention also provides a method for preparing a composite film based on polypropylene carbonate, the preparation method comprising the following steps:
[0020] PBAT, a heat stabilizer, a lubricant and an antioxidant are sequentially added to a mixer, and stirred at 100° C. to 125° C. at a stirring speed of 150 r / min to 200 r / min for 5 min to 10 min to obtain a mixed raw material A for preparing a PBAT heat seal layer;
[0021] The chain extender is added to PPC, heated to 120°C to 130°C, reacted for 20min to 30min, then chloroform is added and ethanol is used for precipitation to remove small molecules, and then the modified composite filler and plasticizer A are added in sequence, and treated at 100°C to 120°C at a stirring speed of 150r / min to 200r / min for 10min to 20min to obtain a mixed raw material B for preparing a modified PPC layer;
[0022] PLA, ethylene-acrylic acid copolymer, antioxidant and plasticizer B are sequentially added into a mixer, and the mixture is stirred at 100° C. to 125° C. for 15 to 20 minutes at a stirring speed of 150 to 200 r / min to obtain a mixed raw material C for preparing a PLA layer;
[0023] Add polyvinyl alcohol, maleic anhydride grafted ethylene polymer and compatibilizer into a mixer, and process at 100° C. to 115° C. at a stirring speed of 150 r / min to 200 r / min for 10 min to 20 min to obtain a mixed raw material D for preparing the first adhesive layer and the second adhesive layer;
[0024] The mixed raw materials corresponding to the PBAT heat sealing layer, the first adhesive layer, the modified PPC layer, the second adhesive layer and the PLA layer are heated and melted by an extruder, and extruded and cast through a T-die. The extrusion temperature is set at 85°C to 180°C, and then biaxially stretched and heat treated in steps to obtain a composite film based on polypropylene carbonate.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention optimizes the raw materials and the ratio of the raw materials for preparing the PBAT heat-sealing layer, the first adhesive layer, the modified PPC layer, the second adhesive layer and the PLA layer, so that the compatibility between the raw materials is increased, and the overall excellent high barrier properties, thermal stability and mechanical properties are exhibited, and the composite film is biodegradable, and is preferably used in the field of environmentally friendly functional packaging to meet market demand.
[0027] 2. The present invention obtains a heat stabilizer by mixing dioctyltin dilaurate and zinc stearate in a mass ratio of 1: (1 to 3) and adding the mixture to the PBAT heat sealing layer, which not only helps to improve the overall performance of the composite film, but also improves the crystallization rate and ductility of the PBAT heat sealing layer, and helps to improve the elongation at break of the composite film.
[0028] 3. The present invention adds a chain extender to the modified PPC layer. After the chain extender reacts with PPC, the end-capping efficiency is high, the chemical action inhibits the unzipping degradation of PPC, and the thermal decomposition temperature is significantly increased. Then, a modified composite filler with excellent compatibility is added to increase the interface effect and hydrogen bonding effect, thereby improving the tensile strength and toughness of the composite film. The components work synergistically with each other to increase the gas passage path, thereby helping to improve the barrier performance.
[0029] 4. The present invention adds a first adhesive layer and a second adhesive layer of specific components, which can form a cross-linking effect with adjacent interfaces during the melt extrusion process, and the interface bonding force is strong, which helps to improve the mechanical properties and barrier properties of the composite film. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0032] A polypropylene carbonate-based composite film in one embodiment of the present invention comprises a PBAT heat-sealing layer, a modified PPC layer and a PLA layer, wherein the PBAT heat-sealing layer and the modified PPC layer are bonded to each other via a first bonding layer, and the modified PPC layer and the PLA layer are bonded to each other via a second bonding layer;
[0033] The PBAT heat seal layer comprises the following raw materials in parts by weight: 100 to 110 parts of PBAT, 7 to 12 parts of heat stabilizer, 1 to 5 parts of lubricant, and 5 to 15 parts of antioxidant;
[0034] The modified PPC layer comprises the following raw materials in parts by weight: 100 to 120 parts of PPC, 15 to 25 parts of chain extender, 1 to 10 parts of modified composite filler, and 1 to 7 parts of plasticizer A;
[0035] The PLA layer comprises the following raw materials in parts by weight: 80 to 100 parts of PLA, 10 to 15 parts of ethylene-acrylic acid copolymer, 1 to 5 parts of antioxidant, and 1 to 5 parts of plasticizer B;
[0036] The first adhesive layer and the second adhesive layer both include the following raw materials in parts by weight: 30 to 45 parts of polyvinyl alcohol, 25 to 35 parts of maleic anhydride grafted ethylene polymer, and 1 to 5 parts of a compatibilizer.
[0037] In one of the embodiments, the heat stabilizer is prepared by mixing dioctyltin dilaurate and zinc stearate in a mass ratio of 1:(1-3).
[0038] In one embodiment, the lubricant is at least one of stearic acid, aluminum stearate, calcium stearate and zinc stearate.
[0039] In one embodiment, the compatibilizer is at least one of PP-g-MAH and ethylene-methyl acrylate copolymer.
[0040] In one embodiment, the chain extender is at least one of isocyanate-maleic anhydride copolymer, styrene-maleic anhydride copolymer and hexamethylene diisocyanate.
[0041] In one embodiment, the modified composite filler is obtained by mixing calcium carbonate and lignin cellulose in a mass ratio of (1-5):1 and then modifying with a silane coupling agent.
[0042] In one embodiment, the modification treatment is: after ball-milling the calcium carbonate and wood cellulose, a silane coupling agent is added at a material-liquid ratio of 1 g / 10 mL, and the mixture is stirred at 65° C. to 75° C. for 30 min to 60 min.
[0043] In one embodiment, the plasticizer A is at least one of poly(1,2-propylene succinate), glycerol and pentaerythritol.
[0044] In one embodiment, the antioxidant is one of antioxidant 1076 and antioxidant 168 or a mixture of both.
[0045] In one embodiment, the plasticizer B is at least one of tributyl citrate, acetyl triethyl citrate, and acetyl tributyl citrate.
[0046] In addition, the present invention also provides a method for preparing a composite film based on polypropylene carbonate, the preparation method comprising the following steps:
[0047] PBAT, a heat stabilizer, a lubricant and an antioxidant are sequentially added to a mixer, and stirred at 100° C. to 125° C. at a stirring speed of 150 r / min to 200 r / min for 5 min to 10 min to obtain a mixed raw material A for preparing a PBAT heat seal layer;
[0048] The chain extender is added to PPC, heated to 120°C to 130°C, reacted for 20min to 30min, then chloroform is added and ethanol is used for precipitation to remove small molecules, and then the modified composite filler and plasticizer A are added in sequence, and treated at 100°C to 120°C at a stirring speed of 150r / min to 200r / min for 10min to 20min to obtain a mixed raw material B for preparing a modified PPC layer;
[0049] PLA, ethylene-acrylic acid copolymer, antioxidant and plasticizer B are sequentially added into a mixer, and the mixture is stirred at 100° C. to 125° C. for 15 to 20 minutes at a stirring speed of 150 to 200 r / min to obtain a mixed raw material C for preparing a PLA layer;
[0050] Add polyvinyl alcohol, maleic anhydride grafted ethylene polymer and compatibilizer into a mixer, and process at 100° C. to 115° C. at a stirring speed of 150 r / min to 200 r / min for 10 min to 20 min to obtain a mixed raw material D for preparing the first adhesive layer and the second adhesive layer;
[0051] The mixed raw materials corresponding to the PBAT heat sealing layer, the first adhesive layer, the modified PPC layer, the second adhesive layer and the PLA layer are heated and melted by an extruder, and extruded and cast through a T-die. The extrusion temperature is set at 85°C to 180°C, and then biaxially stretched and heat treated in steps to obtain a composite film based on polypropylene carbonate.
[0052] In one embodiment, the heat treatment temperature is 90°C to 135°C.
[0053] The above scheme increases the compatibility between the raw materials by optimizing the preparation raw materials and the preparation raw material ratio of the PBAT heat-sealing layer, the first adhesive layer, the modified PPC layer, the second adhesive layer and the PLA layer. The overall structure shows excellent high barrier properties, thermal stability and mechanical properties. The composite film is biodegradable and is preferably used in the field of environmentally friendly functional packaging.
[0054] The embodiments of the present invention will be described in detail below with reference to specific examples.
[0055] Embodiment 1:
[0056] A method for preparing a composite film based on polypropylene carbonate, the preparation method comprising the following steps:
[0057] According to the weight ratio, 100 parts of PBAT, 8 parts of heat stabilizer (dioctyltin dilaurate and zinc stearate in a mass ratio of 1:3), 3 parts of stearic acid and 5 parts of antioxidant 1076 were added to the mixer in sequence, and the mixture was stirred at 100° C. and 150 r / min for 10 min to obtain a mixed raw material A for preparing a PBAT heat sealing layer;
[0058] According to the weight ratio, 20 parts of isocyanate-maleic anhydride copolymer are added to 100 parts of PPC, heated to 120°C, reacted for 30 minutes, then chloroform is added and ethanol is used for precipitation to remove small molecules, and then 7 parts of modified composite filler and 5 parts of poly(1,2-propylene glycol succinate) are added in sequence, and the mixture is treated at a stirring speed of 150r / min at 105°C for 15 minutes to obtain a mixed raw material B for preparing a modified PPC layer; wherein, in this embodiment, the modified composite filler is ball-milled and mixed with calcium carbonate and lignin cellulose in a mass ratio of 3:1, a silane coupling agent is added at a ratio of 1g / 10mL of solid-liquid ratio, and the mixture is modified and treated at 65°C for 30 minutes;
[0059] 100 parts of PLA, 15 parts of ethylene-acrylic acid copolymer, 3 parts of antioxidant 168 and 5 parts of tributyl citrate were added to a mixer in sequence according to weight ratio, and the mixture was stirred at 100° C. and 150 r / min for 15 min to obtain a mixed raw material C for preparing a PLA layer;
[0060] According to the weight ratio, 40 parts of polyvinyl alcohol, 30 parts of maleic anhydride grafted ethylene polymer and 3 parts of ethylene-methyl acrylate copolymer are added into a mixer, and the mixture is stirred at 100° C. and 150 r / min for 15 minutes to obtain a mixed raw material D for preparing the first adhesive layer and the second adhesive layer;
[0061] The mixed raw materials corresponding to the PBAT heat sealing layer, the first adhesive layer, the modified PPC layer, the second adhesive layer and the PLA layer are heated and melted by an extruder, and extruded and cast through a T-die. The extrusion temperature is set to 120°C, and then biaxially stretched in steps and heat treated at 95°C to obtain a composite film based on polypropylene carbonate.
[0062] Embodiment 2:
[0063] A method for preparing a composite film based on polypropylene carbonate, the preparation method comprising the following steps:
[0064] According to the weight ratio, 100 parts of PBAT, 8 parts of heat stabilizer (dioctyltin dilaurate and zinc stearate in a mass ratio of 1:3), 3 parts of aluminum stearate and 10 parts of antioxidant 1076 were added to the mixer in sequence, and the mixture was stirred at 150 r / min for 10 minutes at 110° C. to obtain a mixed raw material A for preparing a PBAT heat sealing layer;
[0065] According to the weight ratio, 25 parts of styrene-maleic anhydride copolymer are added to 100 parts of PPC, heated to 125°C, reacted for 25 minutes, then chloroform is added and ethanol is used for precipitation to remove small molecules, and then 8 parts of modified composite filler and 4 parts of propylene glycol are added in sequence, wherein the modified composite filler is ball-milled and mixed with calcium carbonate and lignin cellulose in a mass ratio of 3:1, and a silane coupling agent is added at a ratio of 1 g / 10 mL of a material-liquid ratio, and stirred for 45 minutes at 70°C; treated at 100°C at a stirring speed of 150 r / min for 15 minutes to obtain a mixed raw material B for preparing a modified PPC layer;
[0066] 100 parts of PLA, 12 parts of ethylene-acrylic acid copolymer, 3 parts of antioxidant 168 and 5 parts of acetyl triethyl citrate were added to a mixer in sequence according to weight ratio, and the mixture was stirred at 150 r / min at 115° C. for 20 min to obtain a mixed raw material C for preparing a PLA layer;
[0067] According to the weight ratio, 42 parts of polyvinyl alcohol, 30 parts of maleic anhydride grafted ethylene polymer and 5 parts of PP-g-MAH were added to a mixer, and the mixture was stirred at 105° C. and 150 r / min for 15 minutes to obtain a mixed raw material D for preparing the first adhesive layer and the second adhesive layer;
[0068] The mixed raw materials corresponding to the PBAT heat sealing layer, the first adhesive layer, the modified PPC layer, the second adhesive layer and the PLA layer are heated and melted by an extruder, extruded and cast through a T-die, the extrusion temperature is set to 120°C, and then biaxially stretched in steps and heat treated at 90°C to 100°C to obtain a composite film based on polypropylene carbonate.
[0069] Embodiment 3:
[0070] A method for preparing a composite film based on polypropylene carbonate, the preparation method comprising the following steps:
[0071] According to the weight ratio, 100 parts of PBAT, 12 parts of heat stabilizer (dioctyltin dilaurate and zinc stearate in a mass ratio of 1:3), 5 parts of calcium stearate and 7 parts of antioxidant 1076 were added to the mixer in sequence, and the mixture was stirred at 150 r / min at 125° C. for 10 min to obtain a mixed raw material A for preparing a PBAT heat sealing layer;
[0072] According to the weight ratio, 25 parts of isocyanate-maleic anhydride copolymer are added to 100 parts of PPC, heated to 120°C, reacted for 30 minutes, then chloroform is added and ethanol is used for precipitation to remove small molecules, and then 9 parts of modified composite filler and 5 parts of poly(1,2-propylene succinate) are added in sequence, wherein the modified composite filler is ball-milled and mixed with calcium carbonate and lignin cellulose in a mass ratio of 3:1, and a silane coupling agent is added at a ratio of 1 g / 10 mL of a material-liquid ratio, and stirred for 45 minutes at 70°C; treated at 120°C at a stirring speed of 150 r / min for 20 minutes to obtain a mixed raw material B for preparing a modified PPC layer;
[0073] 100 parts of PLA, 12 parts of ethylene-acrylic acid copolymer, 4 parts of antioxidant 168 and 5 parts of acetyl tributyl citrate were added to a mixer in sequence according to weight ratio, and the mixture was stirred at 150 r / min at 120° C. for 20 min to obtain a mixed raw material C for preparing a PLA layer;
[0074] According to the weight ratio, 45 parts of polyvinyl alcohol, 35 parts of maleic anhydride grafted ethylene polymer and 5 parts of ethylene-methyl acrylate copolymer were added into a mixer, and the mixture was stirred at 150 r / min for 15 minutes at 110° C. to obtain a mixed raw material D for preparing the first adhesive layer and the second adhesive layer;
[0075] The mixed raw materials corresponding to the PBAT heat sealing layer, the first adhesive layer, the modified PPC layer, the second adhesive layer and the PLA layer are heated and melted by an extruder, and extruded and cast through a T-die. The extrusion temperature is set to 120°C, and then biaxially stretched in steps and heat treated at 95°C to obtain a composite film based on polypropylene carbonate.
[0076] Comparative Example 1:
[0077] The difference between Comparative Example 1 and Example 3 is that no heat stabilizer is added in Comparative Example 1, and the rest is the same as Example 3.
[0078] Comparative Example 2:
[0079] The difference between Comparative Example 2 and Example 3 is that no isocyanate-maleic anhydride copolymer (chain extender) is added in Comparative Example 2, and the other parts are the same as those in Example 3.
[0080] Comparative Example 3:
[0081] The difference between Comparative Example 3 and Example 3 is that no modified filler is added in Comparative Example 3, and the rest is the same as Example 3.
[0082] Comparative Example 4:
[0083] The difference between Comparative Example 4 and Example 3 is that a composite filler (calcium carbonate and lignin cellulose ball-milled in a mass ratio of 3:1) is added to Comparative Example 4, that is, the composite filler is not modified, and the rest is the same as Example 3.
[0084] Comparative Example 5:
[0085] The difference between Comparative Example 5 and Example 3 is that in Comparative Example 5, only calcium carbonate is added, that is, no lignin cellulose is added, and the rest is the same as Example 3.
[0086] Comparative Example 6:
[0087] The difference between Comparative Example 6 and Example 3 is that in Comparative Example 6, only lignin fiber is added, that is, calcium carbonate is not added, and the rest is the same as Example 3.
[0088] Comparative Example 7:
[0089] The difference between Comparative Example 7 and Example 3 is that in Comparative Example 7, epoxy resin is used as the raw material for preparing the first adhesive layer and the second adhesive layer, and the rest is the same as Example 3.
[0090] Comparative Example 8:
[0091] The difference between Comparative Example 8 and Example 3 is that in Comparative Example 8, all the prepared raw materials are added to the mixer in sequence, stirred at 120° C. at a stirring speed of 150 r / min for 20 min, and then melt-casted to obtain a single-layer composite film.
[0092] The composite film samples prepared in Examples 1 to 3 and the composite film comparison samples prepared in Comparative Examples 1 to 8 were subjected to performance tests, wherein the mechanical properties test was determined with reference to GB / T1040.3; the heat seal strength test was determined with reference to GB / T10004-2008; the moisture permeability test was tested with reference to GB1037 "Test Method for Water Vapor Permeability of Plastic Film and Sheet - Cup Method", using a W3 / 031 water vapor permeability tester for 24 hours, with a test pressure of 0.1 MPa; the air permeability test was tested with reference to GB1038 "Test Method for Gas Permeability of Plastic Film and Sheet - Pressure Difference Method", using a Classic2016 pressure difference gas permeator for 24 hours of oxygen permeability test; the heat shrinkage test was tested with reference to STMD1204 standard, with a test temperature of 150°C and a test time of 30 minutes. The results are shown in Tables 1 and 2 below.
[0093] Table 1: Performance test results 1
[0094]
[0095]
[0096] From the data analysis of Table 1, it can be seen that the present invention can ensure the mechanical properties of the composite film by optimizing the composition and process of the composite film so that it meets the use requirements.
[0097] Table 2: Performance test results 2
[0098]
[0099] From the data analysis of Table 2, it can be seen that the composite film prepared in the present application has excellent heat sealing strength and thermal stability, and exhibits relatively excellent barrier properties. The difference between Comparative Example 1 and Example 3 is that no heat stabilizer is added to Comparative Example 1, and the heat sealing strength and barrier properties are good, but worse than Example 3, and the thermal stability is significantly worse than Example 3, indicating that the addition of a heat stabilizer helps to improve the overall thermal stability of the composite film; the difference between Comparative Example 2 and Example 3 is that no isocyanate-maleic anhydride copolymer (chain extender) is added to Comparative Example 2, and the heat sealing strength and barrier properties are significantly worse than Example 3, and the thermal stability is also worse than Example 3, indicating that the addition of an isocyanate-maleic anhydride copolymer (chain extender) helps to improve the crosslinking of the composite film and improve the composite The interaction between the components of the film promotes the barrier properties; the difference between Examples 3 to 6 and Example 3 is the use of modified composite fillers. It can be seen that the addition of modified composite fillers also has a synergistic effect, which promotes the mechanical properties and barrier properties of the composite film; the difference between Example 7 and Example 3 is that in Example 7, epoxy resin is used as the raw material for preparing the first adhesive layer and the second adhesive layer. It can be seen that the heat-sealing strength of the composite film is significantly reduced, and the barrier properties are also significantly deteriorated, indicating that the raw materials for preparing the first adhesive layer and the second adhesive layer also play a significant role in promoting the barrier properties of the composite film. In the process of Example 8, the raw materials of the present application are added to the mixer in sequence for melt casting to obtain a single-layer structure film, but its barrier properties are worse than the barrier properties of the multi-layer structure composite film in Example 3, indicating that the present application has also made optimizations in the structure of the composite film. In the case of interaction between components, the barrier properties of the composite film are further promoted through the interaction of different film layer structures, making it more in line with the market's usage needs.
[0100] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0101] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A composite film based on polypropylene carbonate, characterized in that: The polypropylene carbonate-based composite film includes a PBAT heat-sealing layer, a modified PPC layer and a PLA layer, wherein the PBAT heat-sealing layer and the modified PPC layer are bonded to each other via a first bonding layer, and the modified PPC layer and the PLA layer are bonded to each other via a second bonding layer; The PBAT heat seal layer comprises the following raw materials in parts by weight: 100 to 110 parts of PBAT, 7 to 12 parts of heat stabilizer, 1 to 5 parts of lubricant, and 5 to 15 parts of antioxidant; The modified PPC layer comprises the following raw materials in parts by weight: 100 to 120 parts of PPC, 15 to 25 parts of chain extender, 1 to 10 parts of modified composite filler, and 1 to 7 parts of plasticizer A; The PLA layer comprises the following raw materials in parts by weight: 80 to 100 parts of PLA, 10 to 15 parts of ethylene-acrylic acid copolymer, 1 to 5 parts of antioxidant, and 1 to 5 parts of plasticizer B; The first adhesive layer and the second adhesive layer both include the following raw materials in parts by weight: 30 to 45 parts of polyvinyl alcohol, 25 to 35 parts of maleic anhydride grafted ethylene polymer, and 1 to 5 parts of a compatibilizer.
2. The polypropylene carbonate-based composite film according to claim 1, characterized in that The heat stabilizer is prepared by mixing dioctyltin dilaurate and zinc stearate in a mass ratio of 1:(1-3).
3. The polypropylene carbonate-based composite film according to claim 1, characterized in that The lubricant is at least one of stearic acid, aluminum stearate, calcium stearate and zinc stearate.
4. The polypropylene carbonate-based composite film according to claim 1, characterized in that The compatibilizer is at least one of PP-g-MAH and ethylene-methyl acrylate copolymer.
5. The polypropylene carbonate-based composite film according to claim 1, characterized in that The chain extender is at least one of isocyanate-maleic anhydride copolymer, styrene-maleic anhydride copolymer and hexamethylene diisocyanate.
6. The polypropylene carbonate-based composite film according to claim 1, characterized in that The modified composite filler is obtained by mixing calcium carbonate and lignin cellulose in a mass ratio of (1-5):1 and then undergoing modification treatment with a silane coupling agent.
7. The polypropylene carbonate-based composite film according to claim 1, characterized in that The plasticizer A is at least one of poly(1,2-propylene succinate), glycerol and pentaerythritol.
8. The polypropylene carbonate-based composite film according to claim 1, characterized in that The antioxidant is one of antioxidant 1076 and antioxidant 168 or a mixture of both.
9. The polypropylene carbonate-based composite film according to claim 1, characterized in that: The plasticizer B is at least one of tributyl citrate, acetyl triethyl citrate and acetyl tributyl citrate.
10. A method for preparing a composite film based on polypropylene carbonate, characterized in that: The preparation method is used to prepare the composite film based on polypropylene carbonate according to any one of claims 1 to 9, and the preparation method comprises the following steps: PBAT, a heat stabilizer, a lubricant and an antioxidant are sequentially added to a mixer, and stirred at 100° C. to 125° C. at a stirring speed of 150 r / min to 200 r / min for 5 min to 10 min to obtain a mixed raw material A for preparing a PBAT heat seal layer; The chain extender is added to PPC, heated to 120°C to 130°C, reacted for 20min to 30min, then chloroform is added and ethanol is used for precipitation to remove small molecules, and then the modified composite filler and plasticizer A are added in sequence, and treated at 100°C to 120°C at a stirring speed of 150r / min to 200r / min for 10min to 20min to obtain a mixed raw material B for preparing a modified PPC layer; PLA, ethylene-acrylic acid copolymer, antioxidant and plasticizer B are sequentially added into a mixer, and the mixture is stirred at 100° C. to 125° C. for 15 to 20 minutes at a stirring speed of 150 to 200 r / min to obtain a mixed raw material C for preparing a PLA layer; Add polyvinyl alcohol, maleic anhydride grafted ethylene polymer and compatibilizer into a mixer, and process at 100° C. to 115° C. at a stirring speed of 150 r / min to 200 r / min for 10 min to 20 min to obtain a mixed raw material D for preparing the first adhesive layer and the second adhesive layer; The mixed raw materials corresponding to the PBAT heat sealing layer, the first adhesive layer, the modified PPC layer, the second adhesive layer and the PLA layer are heated and melted by an extruder, and extruded and cast through a T-die. The extrusion temperature is set at 85°C to 180°C, and then biaxially stretched and heat treated in steps to obtain a composite film based on polypropylene carbonate.
Citation Information
Patent Citations
Adhesive films
CN101535434A
Completely biodegradable composite membrane with high barrier property
CN103640290A
Adhesive resin with high oxygen and water vapor resistance
CN104497934A
Polypropylene carbonate composite material for 3D printing and preparation method thereof
CN104693773A
Preparation method of lignin plastic composite
CN107446219A
